Transporte urbano de cargas: estudo de centro de distribuição logística de carga e descarga no município de Cametá-PA - OLIVEIRA, Francieleno Benedito dos Santos (2024)
The study analyzed the feasibility of establishing a logistics distribution center for loading and unloading in the municipality of Cametá-PA, considering the optimization of transport operations and the minimization of the impact on the local community. The general objective of this study is to analyze how the distribution of products occurs in the region of Cametá, with a special focus on the distribution of products, and thus propose suggestions for improvement to the local logistics system. In addition, interviews were conducted with drivers and community members to identify the main problems related to loading and unloading logistics in the region. In addition, the criteria of Morgado et al. (2005) were applied to evaluate different potential locations for the distribution center. The main problems reported by drivers and the community were congestion, noise, and environmental pollution, as well as impacts on local traffic. After the analysis of the criteria of Morgado et al. (2005), it was suggested that the best location for the distribution center is located on the roads of the Trans Cametá-Limoeiro do Ajuru PA-140 road and Avenida Inácio Moura in the Aldeia neighborhood, due to the favorable conditions of cost, environment, sensitivity, and comfort.